2013
DOI: 10.1088/0004-637x/778/2/102
|View full text |Cite
|
Sign up to set email alerts
|

AN INTENSELY STAR-FORMING GALAXY ATz∼ 7 WITH LOW DUST AND METAL CONTENT REVEALED BY DEEP ALMA ANDHSTOBSERVATIONS

Abstract: We report deep ALMA observations complemented with associated HST imaging for a luminous (m UV = 25) galaxy, 'Himiko', at a redshift z=6.595. The galaxy is remarkable for its high star formation rate, 100M ⊙ yr −1 , securely estimated from our deep HST and Spitzer photometry, and the absence of any evidence for strong AGN activity or gravitational lensing magnification. Our ALMA observations probe an order of magnitude deeper than previous IRAM observations, yet fail to detect a 1.2mm dust continuum, indicatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
301
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(355 citation statements)
references
References 93 publications
(129 reference statements)
37
301
11
Order By: Relevance
“…For example, Kanekar et al (2013) searched for [CII] emission from a lensed Lyman-α emitter at z ∼ 6.5, and showed a non detection. Similarly, Ouchi et al (2013) utilized ALMA to search for [CII] from Himiko, a luminous galaxy at z ∼ 6.5 that forms stars at ∼ 100 M yr −1 . These authors showed a non detection to limits L CII < 5.4 × 10 7 L .…”
Section: [Cii] Morphologies and Dynamicsmentioning
confidence: 99%
“…For example, Kanekar et al (2013) searched for [CII] emission from a lensed Lyman-α emitter at z ∼ 6.5, and showed a non detection. Similarly, Ouchi et al (2013) utilized ALMA to search for [CII] from Himiko, a luminous galaxy at z ∼ 6.5 that forms stars at ∼ 100 M yr −1 . These authors showed a non detection to limits L CII < 5.4 × 10 7 L .…”
Section: [Cii] Morphologies and Dynamicsmentioning
confidence: 99%
“…All model variants predict dust masses approximately 0.5 dex larger than those predicted by our fiducial model for galaxies in this stellar mass range. This is driven by higher efficiencies for the condensation of dust in stellar ejecta in the 'no-acc' and 'high-cond' (2015) at z = 3, 4, and 5, and a compilation of data in Mancini et al (2015) at z = 6 and 7, taken from Kanekar et al (2013), Ouchi et al (2013), Ota et al (2014), Maiolino et al (2015), Schaerer et al (2015), and Watson et al (2015).…”
Section: Dust Masses In Galaxiesmentioning
confidence: 99%
“…The simultaneous presence of both dust-rich and dust-(and metal-) poor objects (e.g. Ouchi et al 2013) at high redshift indicates that the transition between these two populations has to be very rapid and may take place on a Myr time-scale (Mattsson 2015). Fig.…”
Section: Elliptical Galaxies: Dust Evolution In the High Redshift Unimentioning
confidence: 99%